DUAL OPTIMIZATION OF MEDIUM COMPONENTS USING WEIGHTED STANDARDIZATION FOR Antibacterial SPECTRUM AND CELL YIELD OF Lactobacillus plantarum SK1305 Isolated from Pickled Pepper - H. Hong; S. Cho; K. Niu; J. Kim; Y. J. Ham; W.D. Lee; S. K. Kim1 (Journal of Animal and Plant Sciences, 2020)
The present study aimed to optimize medium component which maximize antibacterial spectrum and cell yield of Lactobacillus plantarum SK1305 at the same time. L. plantarum isolated from Korean traditional pickled pepper was used and its antibacterial activity against Salmonella typhimurium, Listeria monocytogenes, Burkholderia sp., Enterococcus faecalis, Salmonella gallinarum, and Staphylococcus aureus were investigated. Alteration of medium components was performed using a fractional factorial design and weighted standardization method was applied in optimization of medium components. Inversed probability of medium component effect was employed in weighting. Total of 15 medium ingredients: sucrose, maltose, molasses, yeast extract, corn steep liquor, whey, K2HPO4, MnSO4, MgSO4, tween 80, NaCl, CH3COONa, C6H11NO7, Na2SO4, and FeSO4, were used as variables. The significant positive effects on cell yield were found for maltose and FeSO4. The effects of ingredients on the antibacterial spectrum were summarized using weighted standardization, and sucrose and CH3COONa were determined as the most important ingredients. These results provide useful information about medium ingredients for the improvement of the antibacterial spectrum of L. plantarum SK1305.
Keywords: Lactobacillus plantarum; medium ingredients; antibacterial activity; cell yield; fractional factorial design